2016
DOI: 10.1002/col.22065
|View full text |Cite
|
Sign up to set email alerts
|

A Cross‐cultural comparison of saturation, vividness, blackness and whiteness scales

Abstract: In a typical Euclidean three‐dimensional colour space such as CIELAB, the ‘third‐dimension’, such as CIELAB chroma, has long been criticized as being confusing and difficult to understand for naïve observers and it had relatively poor consistency in visual assessments. As an attempt to find a promising replacement to existing ‘third‐dimension’, two psychophysical experiments were conducted in this study using naïve observers. In the first experiment, 24 Korean observers assessed 48 NCS colour chips in terms of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 25 publications
1
17
0
1
Order By: Relevance
“…This section describes the development of new CAM16 scales of saturation, vividness, whiteness and blackness. The visual data were accumulated by Cho et al [8,9] at Leeds. There are 120 samples specified in XYZ under a fluorescent D65 simulator.…”
Section: Predicting New Colour Scales: Saturation Vividness Whitenementioning
confidence: 99%
See 2 more Smart Citations
“…This section describes the development of new CAM16 scales of saturation, vividness, whiteness and blackness. The visual data were accumulated by Cho et al [8,9] at Leeds. There are 120 samples specified in XYZ under a fluorescent D65 simulator.…”
Section: Predicting New Colour Scales: Saturation Vividness Whitenementioning
confidence: 99%
“…From we learned from above, equations (4) to (7) are proposed to be the baseline scales to develop new saturation (s'), vividness (V), whiteness (W) and blackness (B), respectively. Note that s' is called new saturation here to differentiate the existing s (equation (8)). All baseline equations are based on CAM16 colour coordinates (lightness J, redness-greenness aM, yellowness-blueness, bM).…”
Section: Predicting New Colour Scales: Saturation Vividness Whitenementioning
confidence: 99%
See 1 more Smart Citation
“…[19][20][21] Ackay 22 suggested that colors have different interpretations based on cultures, customs, and ethnic groups, 23 but noted that similarities also exist. A cross-cultural comparison of saturation, vividness, blackness and whiteness scales 24 revealed that Koreans and the British have a similar visual perception of color. Research on perception of color harmony in 2-piece garments showed differences between genders and age groups.…”
Section: Introductionmentioning
confidence: 99%
“…Finalmente, debe destacarse que las preferencias de color residen en aspectos como la cultura, la edad, el sexo o incluso el tamaño del objeto por observar (Park, 2014;63 Prado-León, 2015;Cho et al, 2017a), por lo que su estudio es fundamental para atender las necesidades y preferencias de la sociedad actual (Lee et al, 2013;Michalski, 2014;Yu et al, 2017).…”
unclassified